2008
DOI: 10.1007/s10096-008-0573-8
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of mannose-binding lectin confers protection against tuberculosis in Turkish children

Abstract: Mannose-binding lectin (MBL) plays an important role in innate immunity mediating phagocytosis and activating the MBL complement pathway. Few studies, conducted in adult populations, have shown that genetically determined low MBL levels may confer partial protection against tuberculosis (TB). In this study we aimed to investigate the relationships between the susceptibility to TB and two low producing MBL2 gene polymorphisms (codons 54 and 57) and MBL levels in children. Forty-four TB children (27 pulmonary TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
1
30
2
1
Order By: Relevance
“…Our TB patients show an increased frequency of normal MBL levels, and this is considered a risk for infection due to competitive blocking of the MMR by MBL. While MBL deficiencies confer protection against TB infection [18,[30][31][32][33]. Sarcoidosis is associated with normal MBL levels similar to the healthy population including promoter and structural gene variants [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our TB patients show an increased frequency of normal MBL levels, and this is considered a risk for infection due to competitive blocking of the MMR by MBL. While MBL deficiencies confer protection against TB infection [18,[30][31][32][33]. Sarcoidosis is associated with normal MBL levels similar to the healthy population including promoter and structural gene variants [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The TB group showed higher mean levels than HC, but this failed to reach significance (p=0.098) [18,30]. The literature on Tuberculosis show consistently that low MBL levels confer protection against TB, while higher levels are a risk for active disease [31][32][33]. There is no prior data in the literature for MBL levels in IPF.…”
Section: Mean Mbl Levelsmentioning
confidence: 99%
“…This contrasts with the findings of Selvaraj et al [28], who suggested an association between the AA genotype and extra-pulmonary tuberculosis in patients infected with HIV-1. Cosar et al [22] also observed a significant reduction in the frequency of the AB genotype and the MBL2 ⁄ B allele in patients with extra-pulmonary tuberculosis, although there was no significant difference between the pulmonary patients and the healthy control group. Additionally, Singla et al [29] found the mutant allele MBL2 ⁄ B confers a protective role against TB in the study population.…”
Section: Discussionmentioning
confidence: 92%
“…To date, relatively few studies have investigated the impact of a deficiency of MBL on the susceptibility or resistance of individuals to tuberculosis [16,[20][21][22], and the available data are contradictory in relation to the role of this protein in this susceptibility. While Alagarasu et al [21] concluded that a deficiency of MBL was associated with an increase in susceptibility to tuberculosis, for example, other studies [22,23] indicated that it was associated with resistance to the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation